Figurative Meanings: The (Nightmare Of Translation Procedures) - Elhadi Moh M Ohida; Kirembwe, R.A.H (London Open Academy for Higher Studies, UK, 2024)
The task of translating figurative expressions is a sensitive one, especially in literary writing where the figurative language is an inalienable part of the text as a literary piece. This paper analyzes the fact that translating texts that require transfer of metaphorical and figurative meaning is represents the core of translation challenges. Thus, the paper aims to further elaborate that translating literature texts differs from that of other kinds of writings, due to the different ways in which text is applied. The paper also provides alternative approaches for translating fiction texts. One of the basic objectives highlights those norms and features that distinguish literary texts from non-literary texts. The paper also clarifies that a verse strategy is more influential than a prose strategy in poetry interpretation, because poetic texts require artistic qualities, care and precision. This study uses descriptive analyses procedures, with figurative expressions and images as examples, along with different schools of translation to demonstrate fictional translation difficulties and solutions. Whereupon the paper provides insights on the necessity of using specific translation strategies with rhetorical meanings because rhetorical meanings are different from other types of meanings. The paper ends with a suggestion that translating texts that include metaphorical and figurative meanings calls for a specific approach because it differs from translating other kinds of texts.